Scope of Questionnaires in the Pirls 2021 Study: Lingkup Kuesioner dalam Studi Pirls 2021 - Aziza Amonova (Universitas Muhammadiyah Sidoarjo, 2022)
This presents a concise summary of a scientific article based on the PIRLS-2021 research, focusing on the relationship between the living environment and various factors influencing student learning outcomes. The study aimed to investigate the impact of these external factors on students' educational attainment, employing a comprehensive set of questionnaires to gather relevant data. Through rigorous analysis, the results demonstrated that the living environment plays a crucial role in shaping students' learning experiences and academic achievements. The implications of these findings suggest the necessity of considering external factors and promoting supportive environments to enhance student learning outcomes effectively. This study contributes to the broader understanding of the multifaceted nature of education and emphasizes the importance of holistic approaches in fostering successful learning environments. Highlights: The PIRLS-2021 research examines the influence of the living environment and external factors on student learning outcomes. Comprehensive questionnaires were utilized to collect data and analyze the relationship between the living environment and educational attainment. The study underscores the significance of supportive environments in promoting successful learning outcomes and emphasizes the need for holistic approaches in education. Keywords: PIRLS-2021, living environment, student learning, external factors, educational attainment.